El lenguaje de la traición según Juan Goytisolo, escritor sin tierra - Natale, Daniela (Dialogoi. Rivista di studi comparatistici, 2021)
In this article my aim is to make some observations about Juan Goytisolo’s geographical and linguistic exile. He had chosen to cross the Strait and settle on the other shore, to launch his cultural curse against Spain. In the Trilogía de la traición, the rebellious writer, new Don Julián, renounces his language to seek freer spaces in expression.